Edukasi Pencegahan Covid-19 Dan Pembagian Masker Di Wilayah Kampung Kroyo, Karangmalang, Sragen - Makhabbah Jamilatun; Aisyah Nur Mutmainah (Pengelola Jurnal Politeknik Negeri Ketapang, 2021)
Covid-19 is a disease that develops rapidly and spreading in several countries. Efforts to prevent covid-19 are carried out by the government through the Ministry of Health by instructing awareness and compliance in the use of masks when outdoors. This needs to be done because Covid-19 can be easily transmitted through the respiratory tract and through contact with contaminated surfaces. Based on observations at the beginning of the pandemic, the people around Kroyo Village, Karangmalang, Sragen, have not all understood the prevention of covid-19 and not all people use masks. Therefore, community service activities are carried out with the aim of providing education on the prevention of covid-19 and the distribution of masks in the Area of Kroyo Village, Karangmalang, Sragen. The method of activity used in this community service activity is education to residents about the prevention of Covid-19 and distribution of masks. The result of this community service activity is that people in the Kroyo Village Area, Karangmalang, Sragen understand about the prevention of Covid-19 and understand the importance of implementing health protocols, including using masks as an effort to prevent Covid-19